A Integration of the Global Islamic Capital Market with the Islamic Capital Market in Indonesia: Integrasi Pasar Modal Syariah Global Dengan Pasar Modal Syariah di Indonesia - Alfi Alifi Sirullah (Journal of Economic and Business Analysis, 2023)
This study examines the integration of the Islamic capital market in Indonesia with the Islamic capital market in Malaysia, Japan, China, the United States, and the United Kingdom. This study uses the Vector Error Correction Model (VECM) method and daily closing index data from April 2019 to April 2022. The results of this study indicate the existence of a causality relationship between all Islamic stock indices and in Malaysia, Japan, China, the United States, and the United Kingdom with the Islamic stock index in Indonesia. Then based on cointegration analysis, all Islamic stock indices have a long-term relationship with the Islamic stock index in Indonesia. VECM estimation results show that all Islamic stock indices have a short-term relationship.